Newly Synthesized Melphalan Analogs Induce DNA Damage and Mitotic Catastrophe in Hematological Malignant Cancer Cells - Poczta, Anastazja; Krzeczynski, Piotr; Ionov, Maksim; Rogalska, Aneta; Gaipl, Udo; Marczak, Agnieszka; Lubgan, Dorota (International Journal of Molecular Sciences, 2022)
Myeloablative therapy with highdoses of the cytostatic drug melphalan (MEL) in preparation for hematopoietic cell transplantation is the standard of care for multiple myeloma (MM) patients. Melphalan is a bifunctional alkylating agent that covalently binds to nucleophilic sites in the DNA and effective in the treatment, but unfortunately has limited therapeutic benefit. Therefore, new approaches are urgently needed for patients who are resistant to existing standard treatment with MEL. Regulating the pharmacological activity of drug molecules by modifying their structure is one method for improving their effectiveness. The purpose of this work was to analyze the physicochemical and biological properties of newly synthesized melphalan derivatives (EE-MEL, EM-MEL, EM-MOR-MEL, EM-I-MEL, EM-T-MEL) obtained through the esterification of the carboxyl group and the replacement of the the amino group with an amidine group. Compounds were selected based on our previous studies for their improved anticancer properties in comparison with the original drug. For this, we first evaluated the physicochemical properties using the circular dichroism technique, then analyzed the zeta potential and the hydrodynamic diameters of the particles. Then, the in vitro biological properties of the analogs were tested on multiple myeloma (RPMI8226), acute monocytic leukemia (THP1), and promyelocytic leukemia (HL60) cells as model systems for hematological malignant cells. DNA damage was assessed by immunostaining γH2AX, cell cycle distribution changes by propidium iodide (PI) staining, and cell death by the activation of caspase 2. We proved that the newly synthesized derivatives, in particular EM-MOR-MEL and EM-T-MEL, affected the B-DNA conformation, thus increasing the DNA damage. As a result of the DNA changes, the cell cycle was arrested in the S and G2/M phases. The cell death occurred by activating a mitotic catastrophe. Our investigations suggest that the analogs EM-MOR-MEL and EM-T-MEL have better anti-cancer activity in multiple myeloma cells than the currently used melphalan.
CRIS-Team Scopus Importer:2022-12-09
Keywords: blood cancer; DNA damage γH2AX; drug structure modification; melphalan; mitotic catastrophe